Ethnic Minorities and Regional Development in Asia: Reality and Challenges - Huhua Cao (Amsterdam University Press, 2009)
The development experience in the world over the last century has shown that economic growth cannot be sustained without taking into consideration the social and political development of vulnerable populations, including greater recognition of minority rights. Within this context, the objective of this book is initially to support the interdisciplinary discussion that aims to join studies that surrounding the development of minorities in the Asia.
Keywords: 300; Culture and history; Economics; Sociology